The Role of Fennel Seed Extract on the Expression Pattern of Dysadherin, E-Cadherin and Ki67 in Metastatic Lung Cancer in BALB/C Female Mice - Alireza Mehralikhani; Monireh Movahedi*; Mohaddeseh Larypoor; Fereshteh Golab * (Lorestan University of Medical Sciences, 2021)
Background and Aim: Some herbs have anti-cancer properties such as the anticancer potential of fennel methanolic extract. Metastasis is an undesirable phenomenon that occurs in most cancers. Inhibition of metastatic proteins by fennel extract can increase survival chance. Materials and Methods: Thirty-five adult BALB / C mice were divided into five groups. Four groups were infected with 4T1 cells and one group was considered as healthy control. After one week, three groups were treated with an aqueous extract of fennel seed. The mice were anesthetized after two weeks, and the lung tissues were removed. The expression of Ki67 and dysadherin was evaluated using the qRT-PCR. Moreover, we examined E-cadherin protein expression using the IHC method. Results: Ki67 expression decreased at 100 mg/kg dose (Kruskal-Wallis test: P<0.05) but revealed a remarkable increase at a 200 mg/kg dose (p<0.05). Dysadherin expression significantly decreased at all the three doses (ANOVA test: p <0.05). E-cadherin showed non-significant expression (ANOVA test P>0.05). Conclusion: A 100 mg/kg dose could noticeably decrease the expression of dysadherin and Ki67. The dose of 200 mg/kg can cause a bad prognosis.